Selection and breeding of mungbean - Quah, S. C. (Malaysian Society of Applied Biology, 1987)
Since its early introduction into Malaya (now West Malaysia) in 1917, mungbean (Vigna radiata (L.) Wilczek) has remained a much neglected crop. Its poor grain yield coupled with its unsynchronous flowering habit makes this crop very labour intensive and unprofitable. In 1979, mungbean breeding was initiated in Universiti Pertanian Malaysia with the main objectives of evaluating existing mungbean varieties for grain yield, protein content and other desirable characters and also to develop new varieties through conventional breeding and selection. Early studies indicated that mungbean possessed a significant amount of genetic variation for grain yield, protein content and' other agronomic characteristics. Heterosis was pronounced in both Fl and F2 generations of mungbean crosses. The F2 and F3 populations from these crosses showed an improvement in grain yield when compared to their parents. There was however a slight decrease in 'grain yield in subsequent populations of F4 and FS but the plants in these generations showed more uniformity in plant height and flowering habit. Recently, two F6 lines of V3404 x V3476 were tested in the glasshouse against 27 other accessions from The Asian Vegetable Research and Development Center in the glasshouse. The results indicated that these selections were comparable in grain yield to the advanced lines from AVRDC. They showed not only uniform flowering habit and uniform plant height, but they also have larger seed size and a higher harvest index. Correlation studies indicated that grain yield was positively associated with 100-seed weight, pods/plant, pod length, seeds/plant, plant height at flowering, plant dry weight, harvest index and protein yield but negatively correlated with grain protein content. Grain protein content was found to be positively associated with plant height at maturity.